Apakah Personal Initiative Mahasiswa dapat Dikembangkan dengan Mata Kuliah Character Building? - Antonina Pantja Juni Wulandari (Bina Nusantara University, 2010)
Personal initiative is an active behavior to achieve work’s target, influenced by self-starting aspects, proactive, and toughness in overcoming some constraints. Article presented on how to achieve effectiveness in Character Building subject on personal initiative development based on a research using different group test method. Compared groups were students having finished Character Building subject and not yet followed with the amount of 103 students. Questionnaires consisting of 43 items using semantic different scale were distributed to them. The results indicate that Character Building subject is not effective to develop personal initiative. These are caused by changing happened to students who have followed Character Building subject has not been identified in their personal initiatives, but in the lessening of bad habits in campus life. The students get initiative ability from their personal experience since children to adult. This finding is in line with their participation in organization activities, entrance grade, parents’ jobs, and high school majority which correlating to personal initiative.